2018
DOI: 10.3847/1538-4357/aac025
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Perspective on the Dynamics of G035.39-00.33: The Interplay between Gas and Magnetic Fields

Abstract: Magnetic field is one of the key agents that play a crucial role in shaping molecular clouds and regulating star formation, yet the complete information on the magnetic field is not well constrained due to the limitations in observations. We study the magnetic field in the massive infrared dark cloud G035.39-00.33 from dust continuum polarization observations at 850 µm with SCUBA-2/POL-2 at JCMT for the first time. The magnetic field tends to be perpendicular to the densest part of the main filament (F M ), wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
57
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 133 publications
(182 reference statements)
8
57
0
Order By: Relevance
“…Sanhueza et al (2010) also observed these cores and found molecular outflows associated with cores G34-MM1, MM2, MM3, and MM4. G35 is a filament similar to G34 with several embedded lowluminosity massive protostars (Nguyen Luong et al, 2011) and massive starless clumps (Liu et al, 2018a). A network of filaments covering a broad range of densities is also revealed in G35.…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations
“…Sanhueza et al (2010) also observed these cores and found molecular outflows associated with cores G34-MM1, MM2, MM3, and MM4. G35 is a filament similar to G34 with several embedded lowluminosity massive protostars (Nguyen Luong et al, 2011) and massive starless clumps (Liu et al, 2018a). A network of filaments covering a broad range of densities is also revealed in G35.…”
Section: Introductionmentioning
confidence: 80%
“…Due to low angular resolution (e.g., ∼ 5 ′ with Planck) or high dust extinction (optical or near-infrared polarimetery), previous studies of magnetic fields in filamentary clouds have been mostly limited to nearby clouds. So far, magnetic fields have only been investigated in a few infrared dark clouds (Pillai et al, 2015;Liu et al, 2018a;Juvela et al, 2018;Liu et al, 2018b). Additional observations with higher angular resolution towards filamentary clouds and cores are still needed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, lack of 24 and 70 µm emission does not guarantee a complete absence of star formation activity (e.g., Tan et al 2016;Feng et al 2016b). Several studies have investigated the kinematics and filamentary structure of IRDCs (Busquet et al 2013;Henshaw et al 2014Henshaw et al , 2016Foster et al 2014;Liu et al 2014;Ragan et al 2015;Contreras et al 2016;Lu et al 2018;Liu et al 2018c;Chen et al 2019), their chemistry (Sanhueza et al 2012Sakai et al 2008Sakai et al , 2012Sakai et al , 2015Hoq et al 2013;Miettinen 2014;Vasyunina et al 2014;Feng et al 2016a;Kong et al 2016;Tatematsu et al 2017), molecular outflow content (Sanhueza et al 2010;Wang et al 2011Wang et al , 2014Lu et al 2015;Kong et al 2019), infall (Sanhueza et al 2010;Liu et al 2018a), magnetic fields (Pillai et al 2015;Beuther et al 2018a;Liu et al 2018a;Tang et al 2019), and in the more evolved ones, ultracompact (UC) H ii regions (Battersby et al 2010;Avison et al 2015), thermal ionized jets (Rosero et al 2014(Rosero et al , 2016(Rosero et al , 2019, hot cores…”
mentioning
confidence: 99%
“…The PGCC provides a statistically significant sample to study these questions observationally, although the Planck resolution limits the investigations to structures that are typically much larger than an individual cloud core. However, polarisation of selected PGCCs has already been studied at higher resolution with the SCUBA-2 POL-2 instrument at JCMT (Liu et al 2018c;Juvela et al 2018a;Liu et al 2018b), and many more will be covered by ongoing surveys .…”
Section: Introductionmentioning
confidence: 99%